Pemanfaatan AI Untuk Personalisasi Pembelajaran PAI, Bot Tanya Jawab Fikih, Dan Pembuatan Konten Otomatis - Fika Maqfiroh; Febrianto; Muhammad Zaironi (STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
The rapid development of Artificial Intelligence (AI) has transformed various aspects of education, including Islamic Religious Education (IRE). However, studies integrating AI-based personalized learning, fiqh question-answering chatbots, and automated content generation within a single analytical framework remain limited. Therefore, this study aims to analyze the utilization of AI in personalized Islamic learning, the development of fiqh chatbots, and automated educational content creation, as well as to identify the opportunities and challenges of their implementation in Islamic Religious Education. This study employed a literature review method by examining relevant national and international journal articles, scholarly publications, and academic sources published between 2020 and 2025. The collected data were analyzed using thematic analysis through data reduction, categorization, synthesis, and conclusion drawing. The results indicate that AI supports more adaptive and learner-centered education by enabling personalized learning experiences based on students’ needs and abilities. AI-powered fiqh chatbots improve access to Islamic knowledge through fast and interactive consultation services, while generative AI enhances teachers’ efficiency in developing instructional materials, learning media, and assessment instruments. Nevertheless, the implementation of AI also raises challenges related to the validity of Islamic sources, ethical considerations, data privacy, algorithmic bias, and excessive dependence on automated systems. In conclusion, AI has significant potential to improve the quality and effectiveness of Islamic Religious Education when implemented responsibly under teacher supervision and supported by credible Islamic references. This study contributes to the literature by providing a comprehensive synthesis of AI applications in personalized learning, fiqh chatbots, and automated content generation within the context of Islamic Religious Education, offering a holistic reference for future research and educational practice.